Aggressive Coronary Artery Vasculopathy after Combined Heart–Lung Transplantation. (8th June 2012) - Hayes, Don; Baker, Peter B.; Astor, Todd L.; Preston, Thomas J.; Kirkby, Stephen; Galantowicz, Mark; Hoffman, Timothy M.
ABSTRACT Combined heart–lung transplantation remains as a treatment option for patients with cardiopulmonary failure. There is speculation that lung grafts protect the heart from developing graft vasculopathy after combined heart–lung transplantation. This protective mechanism is more likely, at best, a delay in the onset of coronary artery vasculopathy. We present our experiences in two cases of an aggressive form of cardiac allograft vasculopathy after combined heart–lung transplantation that resulted in the death of both patients.